Parametrična analiza Stirlingove soproizvodne enote na biomaso za uporabo v hišni tehniki - Stritih, Uroš (Strojniški vestnik, 2007)
This paper presents a combined heat and power (CHP) unit using wood biomass to provide an energy supply for housing. The Stirling engine is used as a CHP-producing technology for which a thermodynamic analysis was carried out. The thermodynamic values were mathematically calculated and a computer program for the CHP simulation was written. A parametrical analysis of different combinations of thermodynamic values with respect to the efficiency of the Stirling engine was made. The power of the engine can be changed by the quantity of the working gas, which requires a reservoir. We concluded that if all the isochoric heat were.
Keywords: Stirlingov motor; biomasa; termodinamične lastnosti; učinkovitost; efficiency